Patient Satisfaction and Characteristics of Maternity Room from April to June 2022 at Unggul Karsa Medika Hospital - Theresia Monica Rahardjo; Yoctaf Octora Kadam; Jeffrey Christian Mahardhika (Medical Clinical Update, 2022)
Background Maternal Mortality Rate (MMR) is an indicator that reflects various aspects including the quality of healthcare from clinical standpoint, the quality of healthcare system, the quality of health insurance, the quality of referral systems and non-health aspects that related to healthcare such as economic, social, cultural, and education aspects. In order to reduce MMR, healthcare quality of maternity services should be increased. Patient satisfaction is one of indicators for healthcare quality. In this study, we aim to describe patient satisfaction in maternity room of Unggul Karsa Medika Hospital, Bandung, West Java, Indonesia. Methods This is a quantitative descriptive study conducted in Maternity Room, Unggul Karsa Medika Hospital, Bandung, West Java, Indonesia. The design of the study was cross-sectional. The research was conducted from April to June 2022. Minimal total sample of 97. Total sample that obtained in this study was 150 subjects. Sampling method used in this study was consecutive sampling. Results Percentage of total patient satisfaction of maternity room were slightly increasing from April to June 2022, with highest value was in June 2022 of 94,2%. Four out of six elements of patient satisfaction were increasing, which were speed of services, friendliness and responsiveness, clarity of information and instructions, and completeness of infrastructure and facilities. Conclusion Unggul Karsa Medika Hospital through its excellence service of maternity room has played a significant role to reduce maternal mortality rate in Indonesia, since good and increasing results in patient satisfaction of maternity room service from April to June 2022.